2013
DOI: 10.17795/acr-11488
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Psyllium Herbal Laxative Powder in Prevention of Hemorrhoids and Anal Fissure during Pregnancy, a Randomized Double Blind Clinical Trial

Abstract: A B S T R A C TBackground: Pregnancy and delivery make susceptible women to hemorrhoidal disease and fissure during pregnancy because of an increase in abdominal pressure and constipation. Objectives: We aimed to determine the preventative effect of psyllium powder (herbal laxative) on constipation, anal fissure and hemorrhoidal diseases during pregnancy. Patients and Methods:Regarding the properties of oral psyllium powder, in this study, we aimed to determine the preventative effect of psyllium powder on con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…We read with interest the article published by Ghahramani, et al (1). The research has been well-planned and blinded.…”
Section: Dear Editormentioning
confidence: 99%
“…We read with interest the article published by Ghahramani, et al (1). The research has been well-planned and blinded.…”
Section: Dear Editormentioning
confidence: 99%
“…Dear Editor, Ghahramani et al recently published a well-organized, double blind, placebo-controlled clinical trial concerning the efficacy of psyllium powder laxatives in preventing constipation, hemorrhoids, and anal fissure during pregnancy (1). The authors concluded that psyllium powder consumption used during the third trimester of pregnancy could significantly prevent constipation, hemorrhoid, and anal fissure.…”
mentioning
confidence: 99%
“…It was proven that in the non-pregnant population, the psyllium laxatives increased the frequency of defecation; however, data concerning the treatment of constipation in pregnancy are limited (5). The results of Ghahramani et al (1) suggest that psyllium powder supplementation can be a great resource for pregnant patients with constipation. Since some data suggest that psyllium use might significantly reduce the systolic and diastolic blood pressures in overweight individuals with hypertension, it would be represented as another important indication of its usage (6).…”
mentioning
confidence: 99%